Digital Sin: A Theological Review of Human Sins through Audio-Visual in Digital Realm - Eriyani Mendrofa; Eko Wahyu Suryaningsih; Chang Young Min (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
The development of increasingly advanced Science and Technology has altered various aspects of human life. Whether consciously or not, this development has also impacted the spiritual component of humans. This article discusses how sin can enter human existence through the senses of hearing and sight, beginning with Eve in Genesis 3:15 and continuing to the present day with the widespread use of digital media. The method utilized is a literature review composed of books and journal articles. The findings of this study indicate that digital media can serve as a channel for sin. Humans can sin because of flawed hearing and words. Through the consumption of indecent materials such as pornography, and the unethical use of visual media, digital media sets up the potential for humans to feed their already sinful tendencies. This action demeans human dignity and undermines cherished Christian values. Sinful individuals require pastoral care. Understanding, support, guidance, prayer, prevention, and long-term recovery must be the focus of the ministry for those who have sinned through digital media use. Therefore, a pastor and pastoral counselors must understand the digital world and the challenges people confront in order to approach problems with wisdom and compassion.